Avaliação do Programa de Formação da Escola de Gestão Pública do Estado do Ceará (EGPCE): em múltiplos olhares - Sousa, Palmina Alda Ferreira de (2015)
This dissertation deals with the evaluation of the School Training Program of the State of Ceará Public Management (EGPCE), from the perspective of various subjects who experienced and experience the dynamics of the training courses offered by the Company. The survey was conducted with the subjects makers / program implementers and managers, trainers and course participants of the course Training Information and Communication Technology Managers, based on an integration of data carried out by means of triangulation. The idea was to achieve several subjects at different levels with them interviews and questionnaires were applied. The experience of the selected subjects was the common thread in this research. For this, we selected the 53 subject lines in order to understand the vision they have about the EGPCE training program. The research consisted of two phases: the first, with the application of semi-structured and open interviews, directed the makers / implementers, union representatives, managers, trainers; the second, with the completion of questionnaires by the Group Personnel Development Technician (GTDEP) and by the course participants that course graduates. In total, 44 questionnaires were applied with closed and open questions and interviewed nine people, which resulted in the participation of 53 subjects. Questionnaires and interviews, were the different looks of the subjects on the program and documents to identify the political historical context which involved the creation of EGPCE. Through them, we understand how EGPCE runs the training program for public servants, as well as interpret the proposed formation of EGPCE, comparing it to different paradigms of models Assessment of Public Policies. Finally, based on the testimonies of different subjects who experienced / experiencing the training program, it is undeniable the contribution that EGPCE has been developing as a driver and disseminator of knowledge in public administration at the State Public Administration. The evaluation results indicate the need for diversification of the target audience and the qualitative monitoring of clearance processes and funding for public employees, as union suggestion of the government of the state of Ceará servers. In turn, the makers / implementers propose that more courses contemplate the theme of development of people. Already GTDEP and managers suggest that EGPCE create a routine visit to the organs, so that it can meet the real needs of the institution. Finally, instructors and course participants recommend that EGPCE diversify course offerings and perhaps glimpse to be a corporate university.